FORMULATION AND EVALUATION OF FAST DISSOLVING ORAL FILM OF ANTI-ALLERGIC DRUG - LINKU, ABRAHAM; SIJIMOL, JOSEPH (Asian Journal of Pharmaceutical Research and Development, 2018)
The aim of present work was the development of fast dissolving oral film of Loratadine to overcome the limitations of current routes of administration, to provide immediate action and increase the patient compliance. To improve the bioavailability of the drug, fast dissolving oral film were formulated using different grades of Hydroxy Propyl Methyl Cellulose(HPMC) and various plasticizers like Polyethylene Glycol(PEG) 400, glycerol, Propylene glycol(PG) by solvent casting method. The formulated films were evaluated for film thickness, surface pH, folding endurance, weight variation, % moisture loss, exvivo permeation study, tensile strength, % elongation, drug content uniformity, in vitro dissolution studies,in vitro disintegration test and in vivo study. The optimized formulation (F9) containing HPMC E5 and glycerol showed minimum disintegration time (10.5 s), highest in vitrodissolution (92.5%) and satisfactory stability. Ex vivo permeation study of optimized formulation showed a drug release of 80.6% within 10 min. The milk induced leucocytosis inrat proved that fast dissolving oral films of Loratadine produced a faster onset of action compared to the conventional tablets. These findings suggest that fast dissolving oral film of Loratadine could be potentially useful for treatment of allergy where quick onset of action is required.